Pokémon the movie. Secrets of the jungle [videorecording (DVD)] - Tajiri, Satoshi, 1965- (Pokémon, 2022)
Deep within the Forest of Okoya, the Mythical Pokm̌on Zarude live in a troop and maintain a strict rule that forbids outsiders from entering their territory. Elsewhere in the jungle lives Koko, a human boy raised by a lone Zarude who left the troop. Koko has grown up never doubting that he is a Zarude. But one day, a chance meeting with Ash and Pikachu leaves Koko with his first human friend. Is he truly a Pokm̌on? Or is he, in fact, a human? When danger threatens the jungle, the bonds between Pokm̌on and humans and the love between parent and child will be put to the test.